Sustainable dietary behavior and food choices among sport sciences students: a cross-sectional study within the theory of planned behavior - Eryucel, Mehmet Emre; Cakır, Ayse Sena; Balyan, Melih; Turan, Mehmet Behzat; Cankaya, Cemali; Sahiner Guler, Vesile; Dalbudak, Ibrahim; Pepe, Osman (Frontiers in Nutrition, 2025)
BackgroundSustainable food consumption addresses global environmental challenges and safeguards long-term public health. Understanding how sustainability awareness translates into dietary practices is particularly important among young populations.ObjectiveThis study examined the mediating role of sustainable dietary behavior in the relationship between sustainable consumption tendencies and sustainable food consumption behavior among sport sciences university students, using the Theory of Planned Behavior (TPB) as a partial framework.MethodsA cross-sectional design was applied with 414 Erciyes University Faculty of Sport Sciences students. Data were collected through the Sustainable Consumption Scale, Sustainable Nutrition Behavior Scale, and Sustainable Food Consumption Behavior Scale. Mediation analysis was performed using PROCESS Macro Model 4 with 5,000 bootstrap samples to test indirect effects.ResultsSustainable dietary behavior significantly mediated the association between sustainable consumption and sustainable food consumption behavior (indirect effect = 0.10, 95% CI [0.04, 0.15]). Sub-dimensions such as seasonal and local food choices and waste reduction are strongly linked with sustainable food consumption.ConclusionThe findings suggest that fostering sustainable dietary behaviors is crucial for converting sustainability awareness into concrete dietary practices. University students constitute a key target group for public health and sustainability initiatives, and interventions should emphasize education, accessibility, and awareness to reinforce behavior-based change.